PENGELOLAAN SAPTA PESONA DI OBJEK WISATA PANTAI ARTA INDAH KABUPATEN PADANG PARIAMAN - Yulastra, Roni; Yuliana, Yuliana; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research is aimed to describe the Management (planning, organizing, directing, and controlling) of Sapta Pesona in Tourism Arta Indah Beach Padang Pariaman District which includes: safety, orderliness, attractive, cleanliness, coolness, aminess, and memories. This research is a descriptive research with qualitative data. Technique of collecting data is done by using method of interview, observation, and documentation. This research, we use purposive sampling technique which involves informants, namely: two employees of Youth and Sports Department of Tourism of Padang Pariaman Regency consisting of Section Head of Tourism Facility Development and Infrastructure, and Volunteer Employee (Assistant Head of Section of Development of Facilities and Infrastructure of Tourism), three person employee of Arta Indah Beach Tourist Object, and two staff seller as well as the surrounding community at Arta Indah Beach Tourist Attraction. Data were analyzed by data reduction, data presentation, and conclusion. The results of this study found that: 1). Safety is poor because there are no special security officers available in the tourist area of Arta Indah Beach. 2) The employee are quite capable in maintaining order, but there is no special vehicle parking area in the tourist object. 3) The lack of facilities and infrastructure and the lack of cleanliness of the tourist object makes the less attractive tourist object. 4) Tourist attractions Arta Indah Beach is less clean because of the amount of garbage that is scattered, and lack of existing hygiene support facilities, such as the absence of rubish bin. 5) Attraction Arta Indah Beach is quite cool, but facilities and infrastructure of coolness is less complete because of the absence of parks, gazebos for tourists. 6) The employee are quite kind and friendly towards tourists. 7) Currently there is no provision of specific souvenirs, and on the activities of a particular event in a tourist attraction, beach party events routinely conducted every year.Keywords: Management, Enchantment, Tourism Object